Neurogenic pulmonary edema following intracranial coil embolization for subarachnoid hemorrhage -A case report- - Kim, Jeong Eun (The Korean Society of Anesthesiologists, 2012)
Neurogenic pulmonary edema (NPE) is a well-known complication of acute central neurologic injury, particularly aneurysmal subarachnoid hemorrhage. Both increased intracranial pressure and severe over-activation of the sympathetic nervous system seem to be pathogenetic for the onset of NPE. Although intracranial endovascular therapy is minimally invasive, it may affect brain stem regions and result in sympathetic activation. We now report the case of a 70-year-old woman who suddenly developed pulmonary edema during coil embolization of a ruptured aneurysm. During the intervention, oxygen saturation declined suddenly and a chest radiograph revealed pulmonary edema. The delayed appearance of NPE in this patient implies a risk for sympathetically mediated NPE during endovascular therapy.